RESPONSE Panicum maximum CV. Trichoglume FERTILIZED WITH DIFFERENT TYPES AND DOSAGE OF WASTE VIRGIN COCONUT OIL (VCO) - N. M., WITARIADI; KUSUMAWATI, N. N. C. (Majalah Ilmiah Peternakan, 2022)
An experiment to determine the response of Panicum maximum cv. trichoglume fertilized with different types and dosage of waste Virgin Coconut Oil (VCO). The experiment lasted for 3 months, using 2 factor factorial com- pletely randomized design (CRD). The first factor were waste type of virgin coconut oil (VCO): LA (Original waste VCO) and LT: (fermented waste VCO), and the second factor is fertilizer dosage: D0: 0 l ha-1; D1: 2,500 l ha-1; D2: 5,000 l ha-1; D3: 7,500 l ha-1 and D4: 10,000 l ha-1. From these two factors, 10 treatment combinations were obtai- ned and the treatment was repeated 5 times, there were 50 experimental pots. The variables observed: plant height, number of tillers, number of branches, number of leaves, dry weight of leaves, dry weight of stems, dry weight of roots, total dry weight of forage, leaf area per pot, ratio of leaf dry weight to stem dry weight, and the ratio total dry weight of forage with dry weight of roots. The results showed that there was no interaction between different types and dosage of VCO waste in increasing the growth and production of Panicum maximum cv.Trichoglume. The type of original VCO waste (LA) was able to increase growth on the variable plant height and number of leaves of Pani- cum maximum cv. Trichoglume. Increasing the dosage of VCO waste starting at a dosage of 2,500-10,000 l ha-1 on Panicum maximum cv. Trichoglume can increase growth and production in all variables except root dry weight, leaf dry weight ratio to stem dry weight and total dry weight ratio of forage to root dry weight. It was concluded that the growth and production of Panicum maximum cv. Trichoglume can be increased by fertilizing the original VCO waste type (LA) with the best VCO waste dosage 10,000 l ha-1 (D4).